A Nanopower EEG Low-Pass Filter Using Current-Sharing Vertical Differential Pairs - Pawarangkoon, Prajuab; Ahmad, Rafidah; Abdullah Zawawi, Ruhaifi; Abd Manaf, Asrulnizam; Surakampontorn, Wanlop; Thanapitak, Surachoke (My University, 2025)
A follower-based gm - C low-pass filter that employs CMOS vertical source-couple-pair (VSCP) transconductors is proposed for practical use in EEG acquisition systems. The VSCP transconductor operates as a gm cell with current sharing and linearity enhancement features. It is applied in the first- and second-order gm - C sections cascaded to form a third-order low-pass filter targeting a 150-Hz bandwidth. To mitigate the effects of biasing current source mismatch, dynamic element matching (DEM) is optionally applied to the relevant biasing current source pairs, resulting in second harmonic distortion (HD2) and noise suppression. Implemented in a 0.18-µm process, the proposed filter consumes 16.3-nW power from a 1.2-V supply. Thanks to the DEM and VSCPs, the filter achieves a 150-mVP linear input range [measured at 1% total harmonic distortion (THD)], whereas the input-referred noise of 43 µVrms is obtained leading to a filter dynamic range (DR) of 65.15 dB. Overall performance comparisons with other recent nanopower filters indicate that the figure of merit (FoM) of this proposed filter is comparable, while the linear input range is larger.
Keywords: Biopotential acquisition; EEG; nanopower; source-follower filter